2021
DOI: 10.1136/postgradmedj-2020-139233
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a unique immersive near-peer-led clinical skills educational bootcamp for early-year clinical medical students

Abstract: We establish the development of a unique immersive clinical skills bootcamp for third-year medical students, with formal teaching under five key themes: procedural skills day, examinations, imaging, data interpretation and prescribing. Lastly a simulation event was developed to allow the participants to bring the different themes together, in order to successfully manage an acutely unwell patient for their stage of learning using the newly learnt skills. A 4-week bootcamp was developed and delivered to student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…In virtual reality scenes, synchronized stereo surround sound effects and visual images can further enhance the overall experience of the virtual scene for users. In the system, not only is it necessary to provide simulated sound effects that simulate various real environments, but more importantly, it is necessary for users to feel that they are in the three-dimensional space of the virtual environment and can judge the location of the sound source with both ears [18,19]. For example, when an airplane flies overhead, it feels changes in the sound of approaching from the front, passing over the head, and moving away from the back.…”
Section: Design Of Immersive Virtual Realitymentioning
confidence: 99%
“…In virtual reality scenes, synchronized stereo surround sound effects and visual images can further enhance the overall experience of the virtual scene for users. In the system, not only is it necessary to provide simulated sound effects that simulate various real environments, but more importantly, it is necessary for users to feel that they are in the three-dimensional space of the virtual environment and can judge the location of the sound source with both ears [18,19]. For example, when an airplane flies overhead, it feels changes in the sound of approaching from the front, passing over the head, and moving away from the back.…”
Section: Design Of Immersive Virtual Realitymentioning
confidence: 99%
“…These aspects of the CHESS course may further enhance opportunities for immediate, individual feedback. Another undergraduate clinical skill course similarly showed that students particularly valued group learning, clinically-based scenarios, and specific feedback (26). For other educators planning simulated skills training, these techniques for allowing feedback are assets to a course.…”
Section: Discussionmentioning
confidence: 99%
“…They suggest using a logbook, along with an increased curriculum focus on providing students with opportunities to perform skills (28). Meanwhile, another group teaching their course across 4 weeks encouraged students to practice taught skills on patients in between the sessions, likening this to a "spiral learning" model wherein concepts are revisited in increasing detail (26). With undergraduates increasingly under-exposed and under-confident in practical skills, simulated practice can act as a springboard to encourage students to seek and attempt procedures on patients (29).…”
Section: Discussionmentioning
confidence: 99%